The representation of theater in the nineteenth-century French novel: realism and dramatic Effects - Rondinelli, Bruna G. Silva (Lettres Françaises, 2016)
This article analyzes the way theater, as an artistic and cultural activity, was represented in French novels published between the 1830’s and the 1860’s, such as The Red and the Black, by Stendhal, Lost Illusions, by Balzac, The Count of Monte Cristo, by Dumas (father), The Lady of the Camellias, by Dumas (son), and Madame Bovary, by Flaubert. Analyzing these novels, it was possible to conclude that the references to French theaters, plays, and playwrights emphasize realism and produce a dramatic effect on their characters and actions.